Impact of increased venous pressure on kidney function and mortality in cardiovascular patients with preserved ejection fraction. (3rd March 2020) - Milkas, Anastasios; Tsioufis, Konstantinos; Koliastasis, Leonidas; Tsiamis, Eleftherios; Tousoulis, Dimitris; Bartunek, Jozef; Vanderheyden, Marc
Abstract: Background: Right but not left ventricular hemodynamic parameters have been found to be independently associated with adverse renal outcomes in patients with acute decompensated heart failure (HF). Aim: To investigate the hemodynamic profile of patients without acute decompensated heart failure and left ventricular ejection fraction >50% referred for elective left and right heart catheterization and to correlate left and right filling pressures, stroke volume and arterial blood pressure to renal function parameters. Subsequently, we tested the hypothesis that right ventricle and left ventricle hemodynamic parameters can predict all-cause mortality in our non-HF subjects. Methods: Between October 2009 and November 2010, 151 consecutive patients referred for elective left and right heart catheterization were studied and consequently followed up for a mean period of 8 years in order to identify all-cause mortality. Patient's initial cohort was subdivided in two groups according to right atrial pressure. The RAPRLOW group (Right Atrium Pressure ≤ 9 mmHg) and the RAPRHIGH group (Right Atrium Pressure > 9mmHg) Results: No correlation between blood pressure, pulmonary capillary wedges pressure, cardiac index, stroke volume and stroke volume index (SVI), and parameters of kidney function was observed. However, a weak, although, significant correlation between right atrial pressure (RAP) and modification of diet in renal disease (MDRD) ( r = –0.202; p = .014) could be detected. RAPRLOW patients had a statistically significant lower MDRD value of 16.6 mL/min/1.73 m 2 than RAPRHIGH patients. Increased RAP (HR = 2.03; 95% [CI]: 1.05 to 3.9; p = .025) and age (HR = 1.08, 95% [CI] 1.04–1.12, p < .001) independently predicted all-cause mortality during follow up. Conclusions: Our study demonstrates that right ventricular preload affects renal function in patients with preserved systolic function and that neither aortic systolic pressure nor left ventricle pressure indices were related to estimated glomerular filtration rate. Furthermore, we demonstrate for the first time that an increased RAP is able to predict a worse prognosis in patients with preserved ejection fraction independently of well-established risk factors, such as blood pressure and SVI.